Which urine marker test provides more diagnostic value in conjunction with standard cytology- ImmunoCyt/uCyt+ or Cytokeratin 20 expression - Soyuer Serdar; Tokat Fatma; Sofikerim Mustafa; Soyuer Isin; Ozturk Figen (BMC, 2009)
Abstract Background Because of the poor sensitivity of urinary cytological findings for the diagnosis of especially low grade urinary bladder carcinoma, new molecular diagnostic methods have been proposed. We decided to verify the ImmunoCyt/uCyt+ (UCyt+™) test and cytology combination and cytokeratin 20 (CK20) and cytology combination in urine as possible diagnostic and monitoring tool for bladder cancer. Methods Evaluation of CK20 expression and UCyt+™ was performed in urine of 90 patients of which 54 with bladder cancer with primary/recurrent diagnosis (low grade urothelial carcinoma (LGUC) = 23/8 patients, high grade urothelial carcinoma (HGUC) = 18/5 patients), and 36 patients as control; except of neoplastic bladder disease patients. For the evaluation of the three tests, CK20 and UCyt+™ tests were combined with urine cytology and compared with each other. Results The overall sensitivity detected for each tumor marker was as follows: for urine cytology was 75.9% and UCyt+™ was 83.3%, for CK20 70.4%, while the specificity was 66.7% for urine cytology and 86.1% for UCyt+™ and 83.3% for CK20. The sensitivity of cytology and UCyt+™ combination was higher (88.9%) than the sensitivity cytology and CK20 combination (77.8%). The simultaneous use of the three markers, sensitivity was reaching 92.5%. Conclusion The UCyt+™ test and CK20 expression are valid tools for the performance of adjunctive analyses with conventional cytologic examination.